Improving Rabbit Fertility: The Relationship Between Semen Dilution Rate and Artificial Insemination Effectiveness - Khuong, T. T. T.; Len, H. V.; Trung, T. T. (Faculty of Animal Science, IPB University, 2024)
This study aimed to assess the impact of different dilution ratios of rabbit semen to Tris Citrate Glucose (TCG) extender on doe fertility through artificial insemination in the Mekong Delta region of Vietnam. The experiment included three dilution ratios (1:10, 1:15, and 1:20), with each treatment replicated 12 times. Semen quality variables were evaluated and does were artificially inseminated using a standardized technique. Our findings revealed that the 1:20 dilution exhibited the highest percentage of successful insemination (66.67%) and the shortest gestation period (31.6 days). Furthermore, the 1:20 dilution treatment resulted in an average litter size at birth of 5.25 kits, a litter weight at birth of 290.37 g, and a litter weight at weaning of 1963.04 g. These results suggest that the 1:20 dilution ratio holds promise for artificial insemination in rabbit breeding programs in the Mekong Delta of Vietnam.